Uncovering the Hidden Correlations between Socioeconomic Indicators and Aviation Accidents in the United States - Joana Samarra; Luís F. F. M. Santos; Ana Barqueira; Rui Melicio; Duarte Valério (Applied Sciences, 2023)
Rules and regulations for accident mitigation have been implemented between all players. It is necessary to use new technologies and resources for human factors to mitigate future accidents to decrease accidents. It has been verified that accidents by sabotage are currently non-existent and that most of the fatalities are during the flight and in the runway approach phase. Severe accidents with associated fatalities are a small number that tend to decrease over time. Human errors, although with all the mitigations over time, are still the most significant cause of accidents; although accidents have decreased, other factors may be related to this type of error, such as the lack of personnel for the operation of a flight. Accidents can also be related to other factors, such as economic factors. GDP growth is positively correlated with accidents, and inflation is negatively correlated. It is also found that the inflation factor is also related to the number of flights due to a lack of demand.